PENGARUH PESAN IKLAN TELEVISI GOOGLE VERSI “CARI LIRIK” TERHADAP PENGGUNAAN FITUR OK GOOGLE PADA MAHASISWA DI BANDUNG - Aviesni Sabrina; Berlian Primadani Satria Putri (Dialektika, 2018)
Advertising media is one of the ways to introduce a new product to consumer. One of the advertisement types which has many advantages is television. Google is one company which use television as their advertising media. Researcher chose the "Cari Lirik" version from others Google advertising version on tv. This study reasearch aims is to find out on how big the influence of Google TV advertising messages version of “Cari Lirik” on the use features of ‘OK Google’ to student in Bandung. This study reasearch aims is to find out on The Influence of Google Television Ads Library messages search lyrics to Google's Use of Ok Features in Bandung. The type of this research is used a quantitative type, while the population in the study were student in top 10 University in Bandung. The sample used is 100 respondents by using purposive sampling technique. The results showed a positive influence between elements of advertising ,essages by 36.7 % against the use of ‘OK Google’ features. While the remaining 67.3% influenced by other variables that not included to be researched. Descriptive research results, explain the percentage of responses to Google TV advertising messages version of “Search Lyrics” by 80 % , where the use of the features has 70 % on percentages.